Effect of Added Extra Calcium Carbonate into the Diets, One Hour Before Starting Dark Period on Performance and Egg Quality of Laying Hens - Kermanshahi, H.; Hadavi, A. (International Journal of Poultry Science, 2006)
In order to study the effect of four levels of extra calcium carbonate as limestone (0, 1, 2 and 3 g/hen/day, laying hen size, 3-4 mm) in a finished standard diets of laying hens, one hour before starting dark period, 160 Hy-line W36 laying hens, 85 weeks of age (after force molting) were selected and tested in a completely randomized block design with four treatments and four replicates. In a period of 8 weeks, feed intake (FI), egg weigh (EW), the number of cracked eggs (CE), the number of broken eggs (BE) and hen day egg production (HDEP) recorded daily. Eggshell quality including eggshell weight (ESW) and eggshell thickness (EST) were recorded every two weeks. CE, BE, ESW and EST were significantly improved by adding extra levels of calcium carbonate into the finished diets (P< 0.05). The highest incidence of CE and BE were seen in treatment one (control diet with no added extra calcium carbonate) and the lowest incidence of these traits were seen in treatment four (3 g/hen/day extra calcium carbonate). The best and the worst quality of ESW and EST were also seen in treatment four and one, respectively. Under the conditions of this study, it was concluded that use of 3g/hen/day extra calcium carbonate before starting the dark period in laying hens improves egg quality traits and therefore more benefits to egg producers and more healthy eggs for consumers.